Development of load constant current model using feedback‐controlling resonant switching algorithm for overload protection - Hsiung‐Cheng Lin; Kai‐Chun Hsiao (IET Circuits, Devices and Systems)
Traditional overload protection methods usually use either breakers or converters, focused on the side of power supply. However, these schemes may suffer from a slow response time or load dependence. Particularly, the facility may not be able to remain as a regular working condition when an overload occurs. To resolve this problem, the proposed feedback‐controlling resonant switching algorithm aims to provide an expected load constant current to protect the load from overload without sacrifice for a normal load operation. On the basis of a negative feedback‐control mechanism, the proposed model can detect the load current and thus generate an appropriate switch signal fast and accurately. The switch open period is decided by the model parameters and load current, and it can be set in advance by the timer. On the other hand, the switch closed period is determined by the expected load current that is independent on the load size. The switching acts at the resonant zero‐voltage point, so that no power is consumed during the switching action. The performance simulation with DC 28 V supply confirms that the proposed model can maintain a predefined load constant current for an overload protection effectively.